REDESIGN OF ROAD GEOMETRIC WITH AUTOCAD CIVIL 3D® CASE STUDY: JL. KADIPATEN-KASOKANDEL (STA 0+000-STA 4+800) - Noviar Dwi Hartati; Ade Jaya Saputra; Adinda Fajarika (LEADER: Civil Engineering and Architecture Journal, 2024)
Road geometric planning is part of road development planning which aims to determine the actual dimensions of the road and its function to suit traffic needs. In the geometric planning of the Kadipaten-Kasokandel road at STA 0+000-STA 4+800, geometric patterns and shapes must be planned so that the related streets can produce optimal service to traffic according to their function. Road geometric planning on the Kadipaten-Kasokandel road section from Sta 0+000 to Sta 4+800 using AutoCAD®Civil 3D using the design speed plan (VD) criteria of 80 km/hour, the terrain classification on this road section is flat terrain. In the horizontal alignment, there are four bends with three curves using the Spiral-Circle-Spiral type, while the first use the Full Circle bend type. In the vertical alignment, there are seven segments of the inclined plane.